Efektivitas Wearable Fitness Tracker Dalam Meningkatkan Kebugaran Jasmani Mahasiswa Calon Guru Sekolah Dasar (Studi pada Mahasiswa PGMI) - Aditya Zahran Jibriil Bachdar (Yayasan Al-Afif, 2025)
AbstractThis study aims to analyze the effectiveness of using wearable fitness trackers in improving the physical fitness of male students of the Primary School Teacher Education Study Program (PGMI) at the State Islamic Institute (IAIN) Manado, as an essential preparation for future Elementary School teachers who require optimal stamina1. A quasi-experimental method with a pretest-posttest control group design was employed2. The sample consisted of 40 male students divided into two groups: the experimental group (n=20) used wearable trackers for 6 weeks, while the control group (n=20) did not use any device3. Measurement instruments included standardized physical fitness tests to estimate VO_2 max and physical activity data from the devices4. The results showed a significant improvement in physical fitness in the experimental group with an average VO_2 max increase of 5.7 ml/kg/min, compared to the control group which only increased by 1.2 ml/kg/min (p < 0.05)5. Effectiveness analysis indicated a large effect size (*Cohen’s d = 1.21)6. These findings indicate that wearable fitness trackers are effective in supporting the cardiorespiratory fitness improvement of prospective teachers through self-monitoring mechanisms that enhance physical activity motivation7. This technology is recommended as an educational tool that can be integrated into the PGMI curriculum to create fit and technologically literate teacher role models.